Positive evidence for neonatal imitation: A general response, adaptive engagement. Issue 2 (1st October 2019) - Nagy, Emese; Pilling, Karen; Blake, Victoria; Orvos, Hajnalka
Abstract: The study employed four gestural models using frame‐by‐frame microanalytic methods, and followed how the behaviours unfolded over time. Forty‐two human newborns (0–3 days) were examined for their imitation of tongue protrusion, 'head tilt with looking up', three‐finger and two‐finger gestures. The results showed that all three gesture groups were imitated. Results of the temporal analyses revealed an early and a later, second stage of responses. Later responses were characterized by a suppression of similar, but non‐matching movements. Perinatal imitation is not a phenomenon served by a single underlying mechanism; it has at least two different stages. An early phase is followed by voluntary matching behaviour by the neonatal infant. Abstract : Positive evidence for imitation of four gestures in the first week of life: possible mechanisms and models.